Outpatient prescription practices: A cross-sectional study at an aesthetic hospital, Vietnam, in 2024 - Linh, Nguyen Van; Huy, Le Ngo Khanh; Hue, Vu Thi; Khanh, Tran Nguyen Mai; Duong, Huynh Hai (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2025)
Introduction: Rational drug use is a crucial factor in effective treatment. However, inappropriate prescribing remains common both globally and in Vietnam. In the field of aesthetic surgery, there is a lack of research evaluating outpatient prescribing practices. Objective: To determine the proportion of drugs, prescribing indicators, and drug interactions in outpatient prescriptions for post-aesthetic surgery patients at JT Angel Aesthetic Hospital in 2024. Materials and methods: A cross-sectional descriptive study based on retrospective outpatient prescription data of prescriptions meeting the inclusion criteria at JT Angel Aesthetic Hospital, Vietnam, from August 1st, 2024, to December 31st, 2024. Results: The study included 1,035 aesthetic surgery patients, with females accounting for 95.4%, primarily aged 35 - 59 years (66.4%). The most common surgeries were nasal (32.8%) and eyelid procedures (17.5%). The most frequently prescribed drug groups were antibiotics (99.9%), Analgesics, antipyretics, and anti-inflammatories (99.2%), and digestive medications (91.7%), with amoxicillin + clavulanic acid. Esomeprazole and alphachymotrypsin are the most used. The average number of drugs per prescription was 6.11 ± 1.96. The rate of prescriptions with drug interactions ranged from 46.4% to 47.1%, depending on the database used, with most being moderate or severe interactions. Conclusion: Prescribing practices after aesthetic surgery at the hospital reflected good adherence to prescription regulations, including the use of essential drugs and generic names. However, the high rates of antibiotic and corticosteroid use, along with polypharmacy, highlight the need for monitoring and optimization to ensure rational, safe, and effective drug use for patients.